ANALISIS KORELASI LINGKUNGAN KERJA DAN MOTIVASI KERJA (Studi Pada Bagian Umum Sekretariat DPRD Kabupaten Kutai Barat) - Heti, Heti (PREDIKSI, 2015)
ABSTRACTÂ This study aims to determine whether the work environment has a positive correlation with work motivation.The results showed that there is a positive correlation of the Work Environment variables with variable Work Motivation. It can be seen from the results of statistical test in which the correlation coefficient (r) is equal to 0.683, which means there is a strong relationship between the two variables.Meanwhile if the results are compared with the table Guidelines to provide interpretation of Product Moment Correlation Coefficient, as stated in Chapter III, the results of these calculations are at intervals of 0.60 to 0.799, which means that there is a strong relationship between the Work Environment variables with variable Motivation Work. Thus it can be said that the formulation of the problem in this study have been missed and the proposed hypothesis can be verified.Â